Evaluation of Workers and Customers Exposure to Noise Level in Delta Mall and Robinson Plaza, Delta State, Nigeria - Ado Umar Farouq; Peter I Ahonsi (Graduate Program of Syiah Kuala University, 2018)
This research work titled “Evaluation of Noise Exposure Level in Delta Mall and Robinson Plaza” was aimed at the determination of the noise exposure level and it’s implication to the health of workers/individuals in Delta Mall and Robinson Plaza. A sound level meter (SLM) of model 407736 was used to measure the noise level in Delta Mall and Robinson Plaza. At Robinson plaza, the noise was measured in 13 different locations and they are numbered Block A – N with an exception of Block I. The procedure was carried out in the morning (9:00am – 9:30am), afternoon (1:00pm – 1:30pm), and evening (6:00pm – 6:30pm) measurements for a period of 30 days. The noise exposure level of the entire study area for Robinson Plaza, revealed an average dose of 177.2% and equivalent TWA of 94.1 dBA for 12 hours duration per day and when compared with OSHA standard, it exceeded the exposure action value in the OSHA noise exposure limits (90 dBA for 8 hours duration per day), hence, a detailed risk assessment must be completed for the entire Robinson Plaza. While the noise exposure level of the entire study area for Delta Mall, revealed an average dose of 115.5% and equivalent TWA of 91.0 dBA for 12 hours duration per day and when compared with OSHA standard, it exceeded the exposure action value in the OSHA noise exposure limits (90 dBA for 8 hours duration per day), hence, a detailed risk assessment must be completed for the entire Delta Mall. It’s therefore concluded that the noise generated from both Delta Mall and Robinson Plaza can be harmful to the health of workers. It was recommended that due to these possible effects of noise pollution on the populace, the following action should be carried out: Isolate noise at source, Using protection equipment, Urgent need for legislation to control noise pollution, and Public awakening and education.